2021
DOI: 10.3390/s21144863
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Holographic Sensor for Plankton Studies In Situ including Accompanying Measurements

Abstract: The paper presents an underwater holographic sensor to study marine particles—a miniDHC digital holographic camera, which may be used as part of a hydrobiological probe for accompanying (background) measurements. The results of field measurements of plankton are given and interpreted, their verification is performed. Errors of measurements and classification of plankton particles are estimated. MiniDHC allows measurement of the following set of background data, which is confirmed by field tests: plankton conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…The miniDHC digital holographic camera uses DHC technology [13], which allows to obtain focused images of all particles in the investigated volume. Further image processing includes automatic classification of plankton images according to given taxa [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The miniDHC digital holographic camera uses DHC technology [13], which allows to obtain focused images of all particles in the investigated volume. Further image processing includes automatic classification of plankton images according to given taxa [13].…”
Section: Resultsmentioning
confidence: 99%
“…The miniDHC digital holographic camera uses DHC technology [13], which allows to obtain focused images of all particles in the investigated volume. Further image processing includes automatic classification of plankton images according to given taxa [13]. The automatic classification is based on the following taxonomic features: the size of the plankton, the presence of antennae, and the morphological parameter (the ratio of width to length of the plankton image).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that this energy is sufficient to restore energy used by the battery or the capacitor and continue supplying energy to the sensors. Dyomin et al [ 2 ] developed an underwater holographic sensor to study marine particles, whereas Martins et al [ 3 ] developed and characterized a polyvinylidene difluoride ultrasound transducer to be used as an emitter in underwater wireless communications. In two other articles related to this topic, Nguyen et al [ 4 ] classified underwater sonar images using convolutional neural networks to detect a submerged human body, whereas Sheng et al [ 5 ] proposed a bioinspired twin-inverted multiscale matched filtering method to detect underwater moving targets.…”
mentioning
confidence: 99%
“…Методы цифровой голографии получили широкое практическое применение при исследовании морских взвешенных частиц, в том числе планктона [1]. Регистрация одной цифровой голограммы и последующая ее численная обработка позволяют получить сфокусированные изображения каждой частицы исследуемого объема [2]. Несмотря на преимущества цифровой голографии в восстановленных изображениях возникают шумы и искажения различного происхождения [3,4] -среднеквадратичное отклонение интенсивности в цифровой голограмме размером .…”
unclassified